Electron donor-acceptor interactions in regioselectively synthesized exTTF2-C70(CF3)10 dyads - Takano, Yuta; Angeles Herranz, M.; Martin, Nazario; De Miguel Rojas, Gustavo; Guldi, Dirk Michael; Kareev, Ivan E.; Strauss, Steven H.; Boltalina, Olga V.; Tsuchiya, Takahiro; Akasaka, Takeshi (Chemistry - A European Journal, 2010)
The decakis(trifluoromethyl)fullerene C-CO(CF ) in which the CF groups are arranged on a para-meta-para ribbon of C(CF) edge-sharing hexagons, and which has now been prepared in quantities of hundreds of milligrams, was reacted under standard Bingel-Hirsch conditions with a bis-π-extended tetrathiafulvalene (exTTF) malonate derivative to afford a single cxTTF-C(CF) regioisomer in 80% yield based on consumed starting material. The highly soluble hybrid was thoroughly characterized by using ID H, C, and F NMR, 2D NMR, and UV/Vis spectroscopy; matrix-assisted laser desorption ionization (MALDI) mass spectrometry; and electrochemistry. The cyclic voltammogram of the exTTFC(CF) dyad revealed an irreversible second reduction process, which is indicative of a typical retro-Bingel reaction; whereas the usual phenomenon of exTTF inverted potentials (E>E), resulting in a single, two-electron oxidation process, was also observed. Steady-state and time-resolved photolytic techniques demonstrated that the C-C(CF)singlet excited state is subject to a rapid electron-transfer quenching. The resulting charge-separated states were identified by transient absorption spectroscopy, and radical pair lifetimes of the order of 300 ps in toluene were determined. The exTTFC(CF), dyad represents the first example of exploitation of the highly soluble trifluoromethylated fullerenes for the construction of systems able to mimic the photosynthetic process, and is therefore of interest in the search for new materials for photovoltaic applications. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA,.